Emissions and potential tracer screening of semivolatile/intermediate-volatility organic compounds from urban vehicle fleets - Yajun Wu; Jianfei Peng; Xiaoguo Wang; Peiji Liu; Yan Liu; Fuyang Zhang; Jinsheng Zhang; Bin Sun; Jingqiao Zhang; Kai Song; Pengfei Song; Lin Wu; et al. (npj Climate and Atmospheric Science)
Abstract Semi-/intermediate volatile organic compounds (S/IVOCs) are important precursors for secondary organic aerosols (SOA) and ozone formation. Vehicle emissions from real-world vehicle fleets are significant anthropogenic source, but their emission profiles and chemical fingerprints remain inadequately characterized. Here, we combined tunnel observation with comprehensive two-dimensional gas chromatography coupled with time-of-flight mass spectrometry to investigate vehicular S/IVOCs emissions. We identified 256 vehicle-related compounds with fleet-average emission factors (EFs) of 16.4 ± 12.1 mg·km−1·veh− 1, comprising 67.2% VOCs, 24.3% IVOCs, and 8.5% SVOCs. VOCs accounted for the majority of ozone formation potential (OFP, 84.8%), whereas VOCs, IVOCs, and SVOCs contributed to SOA formation potential at different times. Importantly, our speciated-based SOA estimation enhanced SOA production estimates by 44.1–76.9% compared to traditional approach. We identified eight potential vehicle-related tracers in S/IVOC range through volcano plots and hierarchical clustering analysis, which could benefit future source apportionments. Our work also offers a novel perspective for screening tracers from various sources beyond vehicle-related emissions.